Guinea-Bissau : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2007)
This paper presents an overview of the National Poverty Reduction Strategy Paper (NPRSP) for Guinea-Bissau. The paper discusses the phenomenon of poverty, its dimensions, extent, and distribution by category and region. It provides a background analysis of developments in poverty based on the diagnostic of past economic policies. The paper presents the priority goals in the fight against poverty by articulating a long-term and medium-term vision as well as strategic actions. The operational strategies and strategic actions of the NPRSP are also presented in the paper.